A Study on Customer's Satisfaction towards Service Quality of Organized Retail Stores in Haryana - Malik, Manju (Indian Journal of Marketing, 2012)
The main purpose of this study was to determine the perception of service quality of organized retail stores and their satisfaction among 500 respondents from organized retail outlets selected from Haryana, and across these dimensions: Product aspects, Price aspect, Physical aspect, Promotional schemes, and Personnel Interaction and After Sales Services. The study also investigated differences between the dimensions of service quality of organized retail stores and demographic variables: age, gender and annul income, and the relationship between service quality of retail stores and the customer satisfaction as dependent variables. Statistical tools used were frequency counts, percentages, means, One-Way ANOVA and Pearson's. Analyses were done using the SPSS for Windows (Version 10.0) computer software and set at 0.05 level of significance. Across the sub-dimensions of service quality of organized retail stores, the respondents' level of perception and satisfaction in terms of Product aspects, Price aspect, Physical aspect, Promotional schemes, Personnel Interaction and After sales services was "good". There was a significant difference between the Price aspect and gender and age of the respondents. In terms of dimensions of service quality of organized retail outlets, significant differences were also noted between Physical aspects, Promotional schemes and Personnel interaction and After sales services, when respondents were grouped by age and annual income.